Effects of temperature on the embryonic development and hatchling size of Betaeus emarginatus (Decapoda: Caridea: Alpheidae) - Wehrtmann, Ingo S. (2003)
Betaeus emarginatus is an alpheid shrimp inhabiting rock pool environments characterized by strong fluctuations of ambient factors. Here we describe the embryonic development of B. emarginatus, and analyse the effects of three different temperatures (13, 15 and 20°C) on the duration of the incubation period, egg volume, and the size and morphology of newly hatched larvae. The sequence of embryonic development followed the general patterns described for decapods. Temperature affected the duration of the incubation period, which varied between 66.8 days (13°C) and 22.7 days (20°C). Independent of the thermal regime, eye pigment appeared after completing approximately 50% of the incubation time. Despite almost an identical initial egg volume in all three treatments, there was an inverse relation between temperature and final volume: eggs incubated at 13°C were substantially bigger (471.5mm3) than those maintained at 15 (403.3mm3) and 20°C (387.6mm3). The size of the hatchlings increased significantly with decreasing incubation temperature. However, morphological variability of selected larval characters was generally higher at elevated temperatures. We compare the results obtained with those reported for other decapods inhabiting temperate waters, and discuss the question of why larvae of B. emarginatus incubated at higher temperatures hatch at a smaller size compared to those incubated at lower temperatures.